2010
DOI: 10.1051/0004-6361/200913392
|View full text |Cite
|
Sign up to set email alerts
|

TANGO I: Interstellar medium in nearby radio galaxies

Abstract: Context. Powerful radio-AGN are hosted by massive elliptical galaxies that are usually very poor in molecular gas. Nevertheless, gas is needed at their very center to feed the nuclear activity. Aims. We study the molecular gas properties (i.e., mass, kinematics, distribution, origin) of these objects, and compare them with results for other known samples. Methods. At the IRAM-30m telescope, we performed a survey of the CO(1-0) and CO(2-1) emission from the most powerful radio galaxies of the Local Universe, se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 63 publications
12
81
1
Order By: Relevance
“…Systematic studies of the cold, molecular gas component are now starting. However, Flaquer et al (2010) found that radio galaxies tend to have relatively low molecular gas masses. Given the limited sensitivity of current instruments, ALMA will make a major leap in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic studies of the cold, molecular gas component are now starting. However, Flaquer et al (2010) found that radio galaxies tend to have relatively low molecular gas masses. Given the limited sensitivity of current instruments, ALMA will make a major leap in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of the subclass of radio-loud early type galaxies yield similar rates of H i and CO detections (e.g. Emonts et al 2010;Ocaña Flaquer et al 2010) suggesting no major difference in cold gas mass content between radio-loud and radioquiet early-type galaxies. Differences between radio-loud and radio-quite objects may instead be related to gas kinematicsbecause in order to fuel a black hole gas needs to be transported to the inner few tens of parsec.…”
Section: Introductionmentioning
confidence: 86%
“…Hence, the H 2 gas that comprises the bulk of the molecular interstellar medium (ISM) is commonly believed to be too cold to be visible. And yet, despite these observational disadvantages, the advent of the Infrared Space Observatory and in particular Spitzer's Infrared Spectrograph (IRS, Houck et al 2004) revealed pure rotational H 2 emission from a rich variety of extragalactic sources, including normal star-forming galaxies (Roussel et al 2007), ultraluminous and luminous infrared galaxies (U/LIRGs Lutz et al 2003;Veilleux et al 2009;PereiraSantaella et al 2010;Stierwalt et al 2014), galaxy mergers (Appleton et al 2006), radio-loud active galactic nuclei (AGNs) (Ocaña Flaquer et al 2010), UV-selected galaxies (O'Dowd et al 2009), quasar hosts (Evans et al 2001), cooling-flow cluster systems (Egami et al 2006), sources with extreme shockdominated energetics (Ogle et al 2010), and even star-forming sources at redshifts 2 ).…”
Section: Introductionmentioning
confidence: 99%